Prevalence of Drug-Resistant Extrapulmonary Tuberculosis in Thailand from 2023 to 2024 - Nasrisuk, Thipparat (Disease Control Journal, 2026)
Drug-resistant tuberculosis (DR-TB) is a major global public health concern. Physicians are usually aware of the occurrence of drug-resistant pulmonary tuberculosis (DR-PTB) but lack concern about Drug-resistant extrapulmonary TB (DR-EPTB). DR-EPTB poses a formidable diagnostic, therapeutic challenge. There is limited information available about the drug resistance patterns in extrapulmonary tuberculosis (EPTB) and prevalence of DR-EPTB remain limited. This retrospective study aimed to determine the prevalence of DR-EPTB among 373 EPTB patients who underwent drug susceptibility testing (DST) for first (FLDs) and second-line drugs (SLDs) at the National Tuberculosis Reference Laboratory (NTRL) between 2023 and 2024. The results showed that among the 373 EPTB cases, 14.21% (n=53; 95% CI: 11.01-18.14) were drug-resistant EPTB, with a mean (±SD) age of the patients was 43.88±18.23 years, and a male predominance of 54.29% (95% CI: 42.70-65.43). Most drug-resistant cases occurred among previously treated patients 86.67% (95% CI: 73.45–94.12). The prevalences of drug resistant EPTB were isoniazid 10.46% (95% CI: 7.72-14.00), rifampin 6.17% (95% CI: 4.10-9.12), ethambutol 0.27% (95% CI: 0.01-1.66), levofloxacin 0.94% (95% CI: 0.19-2.85) and multidrug-resistant EPTB was 3.22% (n=12; 95% CI: 1.79-5.60). Specimen with MDR prevalence was found to be: pus 75%, blood 17% and pleural fluid 8%. Drug resistance, including isoniazid-resistant, rifampin-resistant was observed in a significant proportion of extrapulmonary specimens referred for DST. Access to culture and DST for extrapulmonary specimens should be expanded. Guidelines for drug-resistant management should have explicit sections on extra-pulmonary tuberculosis.